2018
DOI: 10.1051/0004-6361/201833124
|View full text |Cite
|
Sign up to set email alerts
|

A unified accretion-ejection paradigm for black hole X-ray binaries

Abstract: Context. It has been suggested that the cycles of activity of X-ray binaries (XRB) are triggered by a switch in the dominant disk torque responsible for accretion. As the disk accretion rate increases, the disk innermost regions therefore change from a jet-emitting disk (JED) to a standard accretion disk (SAD). Aims. While JEDs have been proven to successfully reproduce X-ray binary hard states, the existence of an outer cold SAD introduces an extra nonlocal cooling term. We investigate the thermal structure a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 79 publications
1
54
0
Order By: Relevance
“…Within this paradigm, the accretion flow has two constituents: an outer SAD, extending down to a transition radius r J where the magnetization becomes of order unity, and an inner JED down to the innermost stable circular orbit (ISCO). When the transition radius is close to the ISCO, the thermal emission from the SAD dominates and the source is in a soft state; for large transition radii, the X-ray emission from the JED dominates and the source is in a hard state (for details, see Marcel et al 2018a). In addition to the transition radius, the other crucial parameter is the accretion rate, which determines the total luminosity and influences the aspect ratio of the disc height to radius (Marcel et al 2018b).…”
Section: Testing the Jet-emitting Discmentioning
confidence: 99%
See 3 more Smart Citations
“…Within this paradigm, the accretion flow has two constituents: an outer SAD, extending down to a transition radius r J where the magnetization becomes of order unity, and an inner JED down to the innermost stable circular orbit (ISCO). When the transition radius is close to the ISCO, the thermal emission from the SAD dominates and the source is in a soft state; for large transition radii, the X-ray emission from the JED dominates and the source is in a hard state (for details, see Marcel et al 2018a). In addition to the transition radius, the other crucial parameter is the accretion rate, which determines the total luminosity and influences the aspect ratio of the disc height to radius (Marcel et al 2018b).…”
Section: Testing the Jet-emitting Discmentioning
confidence: 99%
“…In addition to the transition radius, the other crucial parameter is the accretion rate, which determines the total luminosity and influences the aspect ratio of the disc height to radius (Marcel et al 2018b). The evolution of transition radius and accretion rate can explain the spectral properties of X-ray binaries like GX 339-4 during outbursting cycles (Marcel et al 2018a(Marcel et al , 2019.…”
Section: Testing the Jet-emitting Discmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing so, gravitational energy is transformed into the kinetic energy of the outflow, thus there is no need for it to be radiated locally in the disk. This action of the large scale magnetic field suppresses the total radiation from the disk and modifies its high-energy spectrum [5,6,7].The study of accretion flows is very complicated by itself. Now that we have concluded that accretion flows co-exist and as it seems do depend strongly on ejection flows, one needs to study accretion and ejection as one coherent process.…”
mentioning
confidence: 99%